Computational models of neuron-astrocyte interaction in epilepsy - Volman, Vladislav; Bazhenov, Maxim; Sejnowski, Terrence J. (Frontiers in Computational Neuroscience, 2012)
Astrocytes actively shape the dynamics of neurons and neuronal ensembles by affecting several aspects critical to neuronal function, such as regulating synaptic plasticity, modulating neuronal excitability and maintaining extracellular ion balance. These pathways for astrocyte-neuron interaction can also enhance the information-processing capabilities of brains, but in other circumstances may lead the brain on the road to pathological ruin. In this article, we review the existing computational models of astrocytic involvement in epileptogenesis, focusing on their relevance to existing physiological data.